Model Pengembangan Wakaf untuk Pemberdayaan Ekonomi Masyarakat pada Peternakan Domba - Lulu Musa Dil Piero; Laily Dwi Arsyanti; Yuda Asnawi; Budi Susilo Setiawan (MALIA: Jurnal Ekonomi Islam, 2022)
The purpose of this study is to produce an empowerment program in order to prosper the community through the management of productive waqf funds with the addition of sheep supply. The development of the livestock waqf program is carried out through the BMC or Business Model Canvas approach which is tested with the Lisrel SEM method. The results of this study indicate that the development of MT Fram farm waqf has shown that many program evaluations must be carried out. The scheme of several business capital canvas indicators from the livestock waqf management program has not been able to run significantly. The standardization value which is less than 1.96 makes several indicators insignificant, including indicators of customer relationship, value proposition, channels, key resources. This means that the livestock waqf management program at MTFarm is feasible to continue to be developed, but it must require more intense effort and guidance to run optimally.